(untitled) (Academicia Globe: Inderscience Research, 2022)
Acinetobacter baumannii is a Gram-negative, coccobacillus, and biofilm-forming bacteria. Aims of the current study is detection, isolation, molecular diagnosis of A. baumanni spp that isolated from hospitalized patients with burns at Baquba Teaching hospital in Diyala province. (50) Samples are collected from patients with burn infections. The findings are included that percentage of isolates of A. baumannii was 10/50 (20%) in burns infections. The samples are cultured on MacConkey, blood, and tested by gram stain and biochemical examination. The confirmed molecular diagnosis of the isolates was made using designed primers of the 16SrRNA gene for the PCR technique. Furthermore, the results include the use of (15) antibiotics against A. baumannii and showed that all clinical isolates were resistant to many antibiotics using the Vitek-2 system. All isolates were resisted (8) tested antibiotics. Imipenem did not affect 90% of A. baumannii. 10% of the isolates were sensitive to Tobramycin, Gentamicin, and Amikacin. 50% of them could resist Trimethoprim-sulfamethoxazole. Finally, all the isolates could not resist Colistin, and 10% showed resistance against Tigecycline and Minocycline. Eight isolates 8/10 (80%), displayed gyrA gene, while 5/10 (50%) of isolates had bla VIM gene. Moreover, all A. baumannii isolates could form biofilms. A. baumannii, one of the most important pathogens, has high resistance to used antibiotics but shows high sensitivity to Colistin, and can generate strong biofilms.